Prevalence of Hypertension Disorders among Adolescent Students in Ghana - Abena Sekyere (Disease and Health Research - New Insights Vol. 1, 2024)
Aims: The main purpose of this study is to investigate the prevalence of hypertension, associated risk factors, and its effect on physical activity in young people aged 14-19 years. Study Design: This is a Cross-sectional study. Place and Duration of Study: Sample: Department of Biochemistry, College of Science, Kwame Nkrumah University of Science and Technology between June 2009 and July 2023. Methodology: A multistage sampling method was used to select 909 youth from three secondary schools (three towns in the Ashanti region of Ghana). The follow-up study was conducted on 142 people with high blood pressure. Anthropometric and blood pressure were measured with approved devices. Measurement of physical activity and dietary intake via survey. Blood pressure was measured using a validated automatic sphygmomanometer, with participants seated comfortably and resting for at least five minutes before measurement. Three readings were taken at one-minute intervals, and the average of the last two was recorded to reduce the impact of stress or short-term changes. Systolic and diastolic blood pressures were the main parameters recorded. Additionally, the study evaluated cardiovascular parameters (heart rate, echocardiography, ECG) and renal parameters (serum creatinine, GFR, urinalysis, BUN). Results: Research shows that the prevalence of high blood pressure is 9.1% and the incidence of prehypertension is 24.8%. The prevalence of high blood pressure is significant by school choice. A majority of men have higher blood pressure than women, with 10.6% having high blood pressure, 46.6% having prehypertension, and 42.6% having high blood pressure. Data shows that 81.6% of participating parents are self-employed. The results show that there is little work, 72.73% of hypertensive patients are not working, while 40.32% and 59.97% of inactive and hypertensive patients are still sedentary. The results showed that MCV was negatively correlated with systolic blood pressure and diastolic blood pressure (r=-0.230, r=-0.183), while MCHC was negatively correlated with systolic blood pressure and diastolic blood pressure (r = 0.171). showed., r = 0.256). RDW-SD was found to be negatively associated with systolic and diastolic blood pressure. There was a negative correlation between P-LCR and systolic and diastolic blood pressure (r=-.185, r=-.167). Conclusion: The research found that blood pressure distribution varied among students in different schools, with the highest levels in KASS (57% hypertensive) compared to KOSS (19%) and BONWIRE (7%) (X^2 = 32.993, df = 4, p < 0.001). Despite examining cultural and lifestyle factors, no significant determinants of hypertension were identified. Lipid analysis also showed no significant differences between blood pressure groups. These findings highlight the need for further research to explore other potential causes of high blood pressure and to develop effective prevention and management strategies.